Examining Clinical Predictors of Change in Recreational Preference Congruence Among Nursing Home Residents Over Time. (November 2017) - Heid, Allison R.; Van Haitsma, Kimberly; Kleban, Morton; Rovine, Michael J.; Abbott, Katherine M.
Objective: There remains a significant gap in the field regarding the measurement of preference-based care over time in nursing homes (NHs). This study discusses the use of a quality indicator that tracks recreational preference congruence (PC; that is, the match between NH residents' important preferences in recreational activities and their weekly attendance in these preferred activities).Method: Using a sample of 199 older adults, we examine the change in PC over 52 weeks using multilevel-mixed effects regression analyses.Results: PC over time is highly variable and residents with greater functional limitations (vision, language comprehension, incontinence) and no diagnoses of mental health or neurological disorders have lower PC over time.Discussion: Certain clinical characteristics have greater impact on resident PC over time. Particular attention needs to be given to the recreational attendance of residents with incontinence, and visual and language comprehension difficulties.